2012
DOI: 10.1002/cbic.201200407
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Encoding of a Bicyclo[6.1.0]nonyne‐Charged Amino Acid Enables Fast Cellular Protein Imaging by Metal‐Free Ligation

Abstract: Visualizing biomolecules by fluorescent tagging is a powerful method for studying their behaviour and function inside cells. We prepared and genetically encoded an unnatural amino acid (UAA) that features a bicyclononyne moiety. This UAA offered exceptional reactivity in strain-promoted azide-alkyne cycloadditions. Kinetic measurements revealed that the UAA reacted also remarkably fast in the inverse-electron-demand Diels-Alder cycloaddition with tetrazine-conjugated dyes. Genetic encoding of the new UAA insid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
136
0
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 163 publications
(149 citation statements)
references
References 53 publications
(34 reference statements)
5
136
0
7
Order By: Relevance
“…This is in line with the fact that BCN undergoes extremely fast IED DielsAlder cycloaddition with 1,2,4,5-tetrazines 20,30,33 , while DIBAC is inert 31 . Fig.…”
Section: Resultssupporting
confidence: 81%
“…This is in line with the fact that BCN undergoes extremely fast IED DielsAlder cycloaddition with 1,2,4,5-tetrazines 20,30,33 , while DIBAC is inert 31 . Fig.…”
Section: Resultssupporting
confidence: 81%
“…For example, Table 1 above displays the reaction rate constants of the known cyclooctynes across these solvents, which in fact makes it difficult to truly compare the usefulness of these probes in a quantifiable manner. Furthermore, it has been noted by several authors that SPAAC proceeds (significantly) faster in more aqueous solvent systems [9,19,24,40,60].…”
Section: Solvent Effectsmentioning
confidence: 99%
“…2) cycloadditions with electron-poor tetrazines [3]. The latter process can be tailored to specific reaction rates with electron-rich cyclooctynes like BCN in organic solvents [15] and was found to proceed at a surprisingly high reaction rates [1000 M -1 s -1 under aqueous conditions when applied for protein labeling [9,34]. We most recently showed that (4 ?…”
Section: Concluding Remarks and Future Prospectsmentioning
confidence: 99%
“…In a broader context, we have demonstrated the unique combination of reaction efficiency and selectivity of cyclooctyne-based chemistry for the conjugation of sensitive (bio)molecules in aqueous systems, which may be readily extended toward the conjugation of BCN-oligonucleotides to azidecontaining solid surfaces, polymers and large proteins. Finally, we [39] and others [40,41] recently demonstrated that cycloadditions of BCN is not limited to azides, but BCN also undergoes extremely fast strain-promoted inverse-electron-demand Diels-Alder cycloaddition (SPIEDAC) with tetrazines. In contrast, benzofused cyclooctynes DBCO and DIBO are inreactive towards tetrazine [42], which further lifts the potential of BCN-modified oligonucleotides for fast and selective bioconjugations, potentially also in vivo [43].…”
Section: Discussionmentioning
confidence: 90%